AN OVERVIEW OF GLOBALIZATION'S IMPACT ON WELFARE: THE CONTRIBUTION OF INTERNATIONAL ORGANIZATIONS TO THE GLOBAL SOCIETY (PANGEEA, 2025)
The phenomenon of globalization has - for a long time and through many of its aspects - been the subject on intense analytical debate. The social indicators show that it had a positive effect on the welfare of many countries' populations, notwithstanding variations in its progress, due to age or nationality. New phenomena like mass migration and redefinitions at the international level of some concepts like that of handicap have determined a visible transition to what nowadays one calls the global society and towards the development of global social policies. A significant contributor to these changes are the international organizations.
Keywords: welfare; global society; international organizations; global social policies